Superior mesenteric artery syndrome post-total proctocolectomy: A challenging post-operative dilemma - Sahu, Subrata Kumar; Deb, Pratap Kumar; Bhattacharyya, Samir; Gupta, Arnab (Indian Journal of Case Reports, 2024)
Superior mesenteric artery (SMA) syndrome is a rare condition characterized by small bowel obstruction due to compression of the third portion of the duodenum by the SMA and the abdominal aorta. Also, known as Wilkie’s Syndrome, it has a reported incidence of 0.1–0.3%. Confirmation of SMA is classically demonstrated by the decreased aortomesenteric angle with dilatation of the second part of the duodenum and compression of the third part. Medical treatment is usually successful in patients with a short history and a relatively minor degree of duodenal stasis. In patients not responding to conservative management, surgical interventions have been implicated. Post-operative incidence of SMA syndrome is still rarer and has been most commonly seen after spinal surgeries. SMA syndrome after colectomies has a few reported cases in world literature. We present a case of SMA syndrome after total proctocolectomy for carcinoma colon with polyposis coli, managed successfully with conservative treatment.